2018
DOI: 10.3390/nu10030336
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mycotoxin Exposure in Breastfeeding Mothers with Celiac Disease

Abstract: Objective: To assess the risk of mycotoxin exposure (aflatoxin M1, ochratoxin A, and zearalenone) in celiac disease (CD) breastfeeding mothers and healthy control mothers, as well as in their offspring, by quantifying these contaminants in breast milk. Study design: Thirty-five breastfeeding women with CD on a gluten-free diet and 30 healthy breastfeeding controls were recruited. Milk sampling was performed three times per day for three consecutive days. Mycotoxin content was investigated by an analytical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
1
23
3
Order By: Relevance
“…In Italy, the AFM 1 contamination was found in four (5%) breast milk samples [ranging from <7 to 140 ng L −1 ; mean = 55.35 ng L −1 (Galvano et al, 2008)]. Another Italian study revealed that AFM 1 was detected in 37% of samples (mean = 12 ng L −1 ± SD = 11 ng ml −1 ; range = 3–340 ng L −1 ) taken from patients ( n = 30) with celiac disease, while in the healthy control group, the mean AFM 1 concentration levels (9 ± 07 ng L −1 ; range = 3–67 ng L −1 ) were lower (Valitutti et al, 2018). The latter results indicate that the exposure of infants can be substantially higher than our estimate depending on the dietary pattern of the mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Italy, the AFM 1 contamination was found in four (5%) breast milk samples [ranging from <7 to 140 ng L −1 ; mean = 55.35 ng L −1 (Galvano et al, 2008)]. Another Italian study revealed that AFM 1 was detected in 37% of samples (mean = 12 ng L −1 ± SD = 11 ng ml −1 ; range = 3–340 ng L −1 ) taken from patients ( n = 30) with celiac disease, while in the healthy control group, the mean AFM 1 concentration levels (9 ± 07 ng L −1 ; range = 3–67 ng L −1 ) were lower (Valitutti et al, 2018). The latter results indicate that the exposure of infants can be substantially higher than our estimate depending on the dietary pattern of the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The mother’s milk may also contain AFM 1 in comparable concentrations to the dairy cow’s milk (Kunter et al, 2017; Radonić et al, 2017; Bogalho et al, 2018; Valitutti et al, 2018; Fakhri et al, 2019a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the presence of both mycotoxins in maize destined for human and animal consumption is regulated (European Commission [EC], 2003, 2006, 2007, 2010). Recently, attention has been focused on some cohort populations, for example toddlers and the elderly, who are sensitive to mycotoxins similarly to babies, but who are not protected by specific regulations (Chen et al, 2018; Papageorgiou et al, 2018; Valitutti et al, 2018; Gummadidala et al, 2019). This further stresses the relevance of mycotoxin co-occurrence and the importance of acquiring knowledge for co-occurrence prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Italy Valitutti et al (2018) 35 (a) 12 (c),(f) 1.6 2.4 1.6 23 (a) 9 (c,g) 1.2 1.8 1.2 Portugal Bogalho et al (2018)…”
Section: Daily Exposurementioning
confidence: 99%